Atomic collisions in solids: Astronomical applications - Baragiola, R.A; Atteberry, C.L; Dukes, C.A; Famá, M; Teolis, B.D (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2002)
Airless bodies in space are subject to irradiation with energetic atomic particles, which generate atmospheres by sputtering and alter the surface composition. Astronomical observations with telescopes and space probes continuously provide new data that require new laboratory experiments for their interpretation. Many of these experiments also serve to expand the current frontier of atomic collisions in solids by discovering previously unknown phenomena. Some of the experimental techniques used in these experiments could find applications in other areas of atomic collisions in solids. We present results from our current experimental research program on sputtering and surface modification of ices and minerals and point out opportunities for research in this area.